(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article analyzes the interrelation between the concepts of idiolect and conceptosphere in a literary text and their significance in the translation process. The research is conducted on the basis of modernist literature, and the general stylistic features characteristic of the works of writers such as E. Hemingway, V. Woolf, W. Faulkner, G. Stein, and F. Scott Fitzgerald are considered as a theoretical context. The author’s idiolect is interpreted as a mechanism that activates conceptual meaning. Practical analytical examples are mainly selected from the works of E. Hemingway. The article substantiates that preserving the conceptual layer in literary translation should not be limited to lexical equivalence alone, but also requires the recreation of idiolectal features.